ANATOMICAL AND MICROSCOPIC FEATURES OF THE ADRENAL GLANDS IN CHILDREN DURING THE NEONATAL PERIOD (Educator Insights: Journal of Teaching Theory and Practice, 2026)
The adrenal glands are paired endocrine organs located above the upper poles of the kidneys, performing vital hormonal and regulatory functions. During life, their structure undergoes significant changes: from relatively large organs in newborns with a prominent fetal cortex, to well-differentiated structures in the postnatal period. The anatomical and microscopic structure of the adrenal glands was studied on 24 corpses of newborn children using anatomical methods (dissection, measurement) and histological methods (hematoxylin-eosin staining, Van Gieson method). The cortical substance is represented by three zones: glomerular, fascicular, and reticular. The medulla is well developed and contains chromaffin cells. In newborns, the fetal cortex occupies a significant part of the organ. The adrenal gland is covered by a connective tissue capsule with predominance of elastic and collagen fibers.